Mutation detection of type Ⅱ hair cortex keratin gene KRT86 in a Chinese Han family with congenital monilethrix - YE, Zhen-zhen; NAN, Xu; ZHAO, Hong-shan; CHEN, Xue-rong; SONG, Qing-hua (Chinese medical journal, 2013)
Background Monilethrix is an autosomal dominant hair disorder characterized clinically by alopecia and follicular papules.In this study,we collected a Han monilethrix family to detect the mutations in patients and investigated the correlation between the genotype and phenotype of monilethrix.Methods In this study,we identified a Chinese family with monilethrix through light microscopic and scanning electron microscopic （SEM） examination.Genomic DNA from peripheral blood samples was prepared.DNA samples from controls and monilethrix patients were subject to polymerase chain reaction （PCR） amplification.Two pairs of primers were used to amplify the seventh exon of KRT86.Mutation screening of the PCR products was detected using direct sequencing.Results Light microscopic examination showed a regular alternate enlargement and narrow area.SEM examination showed that part of the cuticle of the nodules shed and disappeared gradually in the narrow area with granular protrusions on the surface similar to the erosion-like structure.Parallel longitudinal ridge and groovepattern appeared,and the ridges varied in width,like dead wood.A heterozygous transversion mutation c.1204G＞A（p.E402K） in the seventh exon of KRT86 was identified in both patients.Conclusions The mutation of extron 7 of KRT86 identified plays a major role in the pathogenesis of this pedigree with monilethrix,and is a mutation hot spot of KRT86.Further research is needed to explore the relationship between the phenotype and the mutation of the type Ⅱ hair keratin gene KRT86 of monilethrix.